Quality Policy as a Manifestation of Strategic Plan at Bandung lnstitute of Technology,Indonesia - Bijaksana, Satrio; Puradimaja, Deny Juanda (Jurnal Manajemen Teknologi, 2008)
Definition of quality in higher education has changed rapidly, especially in the last two decades, when quality assurance has turned into global issue in higher education management. In that context, Bandung Institute of Technology (ITB) has declared ITB Quality Policy 2006-2010 that symbolizes the institutional commitment to improve the quality in guided, continuous, and accountable manner. The Policy was developed based on the evaluation of the previous policy as well as the 2006-2010 strategic plan of ITB. Other than development guidelines on six different areas, the Policy also consists of a set of indicator and targets. In this conference, we will share the lessons learned from the development and implementation of this Policy.Â Keywords:Â quality policy, Institut Teknologi Bandung (ITB), higher education